NEGATION, INCLUDING, GRADUAL OBLIVION: STATE STRATEGIES ON SOVIET HERITAGE IN GEORGIA, ARMENIA AND AZERBAIJAN - A. A. Tokarev (Vestnik MGIMO-Universiteta)
In the year of 100th anniversary of the October Revolution, the author turns to the question of the Soviet heritage influence on nation- and state-building processes in three countries of the South Caucasus –Azerbaijan,ArmeniaandGeorgia. The article postulates clear differences between the study of postcolonialism and the post-Soviet space, and therefore the author presents his own operationalization of the "imperial heritage" study.The countries of the South Caucasus are compared based on the following criteria: a number of ethnic Russians as the main constituent of the Soviet people living in the country; a status of the Russian language; national symbols (statutes, architecture, Soviet state symbols, the hierarchy of military ranks), and political practices (functioning of the party systems, type of sovereignty, degree of freedom of speech and political competition).StudyingAzerbaijan,ArmeniaandGeorgiadifferently coming out of theUSSRand using the disintegration of theUSSRto construct their national narratives in accordance with their own ideas about the ways of development, the author finds a repetition of the Soviet system elements.Each of the states demonstrates a unique combination of “post-Soviet Soviet” phenomena. The difference lies in the ratio between pro-Soviet and anti-Soviet elements.Azerbaijanseems to maintain a pro-Soviet narrative more than the others. It inherited the Soviet cult of personality and combined this practice with a completely non-Soviet (Eastern) tradition of political dynasties covered by the election system.The Armenian political tradition includes reference to Soviet Armenia as theSecondRepublic, which distinguishes the country from the neighbors who consider themselves to be the successors of the democratic republics that emerged during the Civil War inRussia. Despite competitive elections and free media, the Armenian leadership seeks to establish a political system with a single dominant party and formally maintain electoral competition. This conjunction of Soviet symbols (Armeniadid not carry out systematic decommunization) and political practices is oddly mixed with the image of GareginNzhdeh as “the father of nation”, a person who was accused in theUSSRfor collaborating with the Third Reich.Georgia tries to part with the Soviet Union to the maximum extent at a symbolic level, has made great progress in building formal democratic institutions, but in reality it is still managed through informal procedures, to which discursive and symbolic decommunization did not affect in principle. Discursive and symbolic decommunization had no impact on the way this country is ruled.The study is based on the data from national censuses, sociological studies, texts of official documents and, especially, the invaluable experience of the included observation of symbolic politics in all three countries.